2017
DOI: 10.1590/1677-5449.005317
|View full text |Cite
|
Sign up to set email alerts
|

Aneurismas da artéria e da veia braquial induzidos por uso contínuo de muleta: relato de caso

Abstract: Crutch-induced arterial aneurysm is a rare event and there are no descriptions in the literature of cases with concomitant venous aneurysms. We report the case of a patient who, after prolonged crutch use, presented with acute ischemia of the upper limb secondary to brachial artery aneurysm thrombosis, associated with the incidental finding of brachial vein aneurysms. Although the main cause of acute upper limb occlusion is embolization of cardiac origin, consideration should be given to the possibility of art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…118 It has also been observed that TBAA are not only limited to genetic pathologies, but may also arise as a complication to a systemic pathology that may affect the haemodynamics of the arterial system in a secondary manner. [13][14][15][16][17][18][19][20][21][22][23][24]119 Findings noted in the current review also confirmed of the above theory. It was found that 51.5% patients with TBAA had a history of CRF with AVF creation in the affected limb and received 1-2 RTs.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…118 It has also been observed that TBAA are not only limited to genetic pathologies, but may also arise as a complication to a systemic pathology that may affect the haemodynamics of the arterial system in a secondary manner. [13][14][15][16][17][18][19][20][21][22][23][24]119 Findings noted in the current review also confirmed of the above theory. It was found that 51.5% patients with TBAA had a history of CRF with AVF creation in the affected limb and received 1-2 RTs.…”
Section: Discussionsupporting
confidence: 82%
“…It was observed that the upper end of a crutch put pressure in axilla which gradually damaged the brachial artery wall by pressing it against the humerus bone, causing aneurysm formation. [19][20][21][22][23][24] These findings shed light on the risk of aneurysm development associated with prolonged use of such walking aids and warrant caution to be taken by physicians and physiotherapists. 19 Remaining aetiologies / risk factors that were found included primary/idiopathic aneurysm, connective tissue 118 Symptoms observed were mostly upper extremity swelling and pain.…”
Section: Discussionmentioning
confidence: 99%